Pengaruh Pelaksanaan WFH terhadap Burnout Karyawan dengan Work Family Conflict sebagai Variabel Intervening - Yurisya Maisyiroh (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. This study aims to 1) to determine the level of implementation of Work From Home and Burnout in educational staff at the Islamic University of Bandung 2) To determine the level of implementation of Work From Home to Work Family Conflict in educational staff at the Islamic University of Bandung 3) To determine the level of work family conflict on burnout in education staff at the Islamic University of Bandung. 4) To determine the level of implementation of Work From Home on Burnout with Work Family Conflict as an Intervening Variable for educational staff at the Islamic University of Bandung. In this research, the method used is descriptive and verification method, using a quantitative research approach and operating the calculations using the IBMSPSS 25.0 program. Collecting data obtained through questionnaires, observations, interviews, and literature studies. The sampling technique is probability sampling, namely proportionate stratified random sampling. Respondents in this study were employees of education staff at the Islamic University of Bandung totaling 60 people. The variables studied in this study are the implementation of Work From Home (X), Burnout (Y), Work Family Conflict (Z). The results of this study conclude that there is a low influence between the implementation of work from home on burnout 2) There is a low influence between the implementation of work from home on work family conflict 3) There is a high influence between work family conflict on burnout 4) There is a significant influence from the implementation of work from home home on burnout with work family conflict for education staff employees at the Islamic University of Bandung. Abstrak. Penelitian ini bertujuanuntuk 1) untuk mengetahui tingkat Pelaksanaan Work From Home dan Burnout pada karyawan tenaga kependidikan di Universitas Islam Bandung 2) Untuk mengetahui tingkat pelaksanaan Work From Home terhadap Work Family Conflict pada karyawan tenaga kependidikan di Universitas Islam Bandung 3) Untuk mengetahui tingkat work family conflict terhadap burnout pada karyawan tenaga kependidikan di universitas islam bandung. 4) Untuk mengetahui tingkat pelaksanaan Work From Home terhadap Burnout dengan Work Family Conflict sebagai Variabel Intervening pada karyawan tenaga kependidikan di Universitas Islam Bandung. Pada penelitian ini metode yang digunakan adalah menggunakan metode deskriptif dan verifikatif, dengan menggunakan pendekatan penelitian kuantitatif dan mengoprasikan perhitungannya menggunakan program IBMSPSS 25.0. Pengumpulan data yang diperoleh melalui kuesioner, observasi, wawancara, dan studi pustaka. Teknik penarikan sampel adalah probability sampling yaitu proportionate Stratified Random Sampling. Responden pada penelitian ini yaitu karyawan tenaga kependidikan di universitas islam bandung yang berjumlah 60 orang. Variabel yang dikaji pada penelitian ini yaitu pelaksanaan Work From Home (X), Burnout (Y), Work Family Conflict (Z). hasil penelitian ini menyimpulkan bahwa Terdapat pengaruh rendah antara pelaksanaan work from home terhadap burnout 2) Terdapat pengaruh rendah antara pelaksanaan work from home terhadap work family conflict 3) Terdapat pengaruh tinggi antara work family conflict terhadap burnout 4) Terdapat pengaruh yang signifikan dari pelaksanaan work from home terhadap burnout dengan work family conflict pada karyawan tenaga kependidikan di universitas islam bandung.